A Study on the Effect of Surface Lysine to Arginine Mutagenesis on Protein Stability and Structure Using Green Fluorescent Protein - Sokalingam, Sriram (Public Library of Science, 2012)
Two positively charged basic amino acids, arginine and lysine, are mostly exposed to protein surface, and play important roles in protein stability by forming electrostatic interactions. In particular, the guanidinium group of arginine allows interactions in three possible directions, which enables arginine to form a larger number of electrostatic interactions compared to lysine. The higher pKa of the basic residue in arginine may also generate more stable ionic interactions than lysine. This paper reports an investigation whether the advantageous properties of arginine over lysine can be utilized to enhance protein stability. A variant of green fluorescent protein (GFP) was created by mutating the maximum possible number of lysine residues on the surface to arginines while retaining the activity. When the stability of the variant was examined under a range of denaturing conditions, the variant was relatively more stable compared to control GFP in the presence of chemical denaturants such as urea, alkaline pH and ionic detergents, but the thermal stability of the protein was not changed. The modeled structure of the variant indicated putative new salt bridges and hydrogen bond interactions that help improve the rigidity of the protein against different chemical denaturants. Structural analyses of the electrostatic interactions also confirmed that the geometric properties of the guanidinium group in arginine had such effects. On the other hand, the altered electrostatic interactions induced by the mutagenesis of surface lysines to arginines adversely affected protein folding, which decreased the productivity of the functional form of the variant. These results suggest that the surface lysine mutagenesis to arginines can be considered one of the parameters in protein stability engineering.